Analysis of Elementary School Students' Science Process Skills in the Merdeka Curriculum - Indri Andriani Astuti; Andi Suhandi; Wahyu Sopandi; Atep Sujana; Gayatri Nurnaningrum (Jurnal Penelitian Pendidikan IPA, 2025)
Science literacy in Indonesia is still far below the global average, thus highlighting the need for substantial improvement in science education, especially in science process skills. This study aims to analyze the basic science process skills of 4th grade elementary school students by using a descriptive approach through classroom observation and written tests. The results showed an average score of 54, categorized as poor, with the score of each aspect being observing 62 (fair), interpreting 61 (fair), classifying 56 (poor), predicting 54 (poor), planning experiments 51 (poor), and communicating 42 (bad). The study identified weak communication and experiment planning skills as the main factors contributing to low science literacy. Therefore, the implementation of inquiry-based learning strategies is essential to enhance science process skills and improve overall science literacy. The findings provide valuable insights for educators to design more effective and engaging science learning in primary schools.